Stressors Contributing To Depression Among First Year Medical Student - Abdullah, Norida; Shonubi, Olurotimi Adebayo; Vazeer Alam, Azra Tasneem (Penerbit Universiti, UTeM, 2017)
Stress is the negative emotional and physiological process that occurs as individuals try to adjust or to deal with the stressors which are environmental circumstances that disrupt or threaten to disrupt individuals daily functioning. The aim of this study to explore the psychological effects of distress and its contributing stressors among first year medical student primarily to investigate the prevalence of depression and stress levels and factors contributing stress among first year medical students’ enrolled in Bachelor of Medical and Surgery in MARA University Technology (UiTM) Sungai Buloh Campus. The researcher intends to distribute questionnaire to the study participants through convenience sampling using the MSSQ stable psychometric instrument to measure sources of stress among medical students and at the same time putting into consideration all ethical practices.